Curve Fitting Kurva Tegangan Keluaran Sensor GP2Y0A02YK untuk Unjuk Kerja yang Lebih Akurat - Priyanto, Agung; Buntoro Irawan; Titik Rahmawati; Ari Cahyono (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Sensors in the internet of things (IoT) and wireless sensor networks (WSN) for various purposes often require recalibration. The datasheet that accompanies the sensor usually displays a table of sensor’s output with minimum, typical and maximum values. This means that there is a tolerance of the values ​​that are still allowed by the manufacturer. For sensors with variable output voltage, it is usually displayed graphically. If the graph is not linear, curve fitting is needed to obtain the curve equation. In this research, curve fitting will be carried out using the least sum of squared errors method using a matrix. The curve equation resulting from curve fitting is needed for data processing or if it is needed to predict fixed variables if the independent variables are known. One of the sensors that has an output voltage curve that is not a straight line is the distance sensor from Sharp, the GP2Y0A02YK series. According to the datasheet, this sensor can be used to measure distances from 20 centimeters to 150 centimeters. The graph of the output voltage measuring distances from 20 cm to 150 cm is in the form of a curved curve. With calibration using curve fitting, it is hoped that the accuracy of sensor measurements and the processing of its output data will increase.